Stenotrophomonas maltophilia virulence and specific variations in trace elements during acute lung infection: implications in cystic fibrosis. - Arianna Pompilio; Domenico Ciavardelli; Valentina Crocetta; Ada Consalvo; Roberta Zappacosta; Carmine Di Ilio; Giovanni Di Bonaventura (PLoS ONE)
Metal ions are necessary for the proper functioning of the immune system, and, therefore, they might have a significant influence on the interaction between bacteria and host. Ionic dyshomeostasis has been recently observed also in cystic fibrosis (CF) patients, whose respiratory tract is frequently colonized by Stenotrophomonas maltophilia. For the first time, here we used an inductively mass spectrometry method to perform a spatial and temporal analysis of the pattern of changes in a broad range of major trace elements in response to pulmonary infection by S. maltophilia. To this, DBA/2 mouse lungs were comparatively infected by a CF strain and by an environmental one. Our results showed that pulmonary ionomic profile was significantly affected during infection. Infected mice showed increased lung levels of Mg, P, S, K, Zn, Se, and Rb. To the contrary, Mn, Fe, Co, and Cu levels resulted significantly decreased. Changes of element concentrations were correlated with pulmonary bacterial load and markers of inflammation, and occurred mostly on day 3 post-exposure, when severity of infection culminated. Interestingly, CF strain - significantly more virulent than the environmental one in our murine model - provoked a more significant impact in perturbing pulmonary metal homeostasis. Particularly, exposure to CF strain exclusively increased P and K levels, while decreased Fe and Mn ones. Overall, our data clearly indicate that S. maltophilia modulates pulmonary metal balance in a concerted and virulence-dependent manner highlighting the potential role of the element dyshomeostasis during the progression of S. maltophilia infection, probably exacerbating the harmful effects of the loss of CF transmembrane conductance regulator function. Further investigations are required to understand the biological significance of these alterations and to confirm they are specifically caused by S. maltophilia.